Global Food Price Inflation and Policy Responses in Central Asia. (IMF Working Papers; Working Paper ;, 2012)
This paper examines the implications of elevated global food prices for inflation in select Central Asian economies - Kazakhstan, the Kyrgyz Republic, Tajikistan, and Uzbekistan. The findings suggest that global food inflation has significant short-run effects that build over time. Inflation outcomes simulated under alternative global wheat price assumptions underscore these vulnerabilities, and suggest that sustained administrative measures are unlikely to prove effective. In line with structural economic features, the interest rate channel of monetary policy is found to be limited, arguing for a broad policy strategy to control more expansive inflationary pressures. Looking ahead, measures to enhance supply responses, deepen domestic financial markets, develop adequate social safety nets, and increase central bank independence are warranted.